Age-Specific Education Inequality, Education Mobility and Income Growth - Jesus Crespo Cuaresma; Samir KC; Petra Sauer (WWWforEurope, 2013)
We construct a new dataset of inequality in educational attainment by age and sex at the global level. The comparison of education inequality measures across age groups allows us to assess the effect of inter-generational education attainment trends on economic growth. Our results indicate that countries which are able to reduce the inequality of educational attainment of young cohorts over time tend to have higher growth rates of income per capita. This effect is additional to that implied by the accumulation of human capital and implies that policies aiming at providing broad-based access to schooling have returns in terms of economic growth that go beyond those achieved by increasing average educational attainment.
Keywords: I24; I25; O50; 330; human capital; education inequality; age structure; economic growth